The The impact of innovation leadership on organizational performance of cooperative: The role of mediating strategic fit - Debi Shintya Dewi; Herri Herri; Ratni Prima Lita (Institute of Computer Science (IOCS), 2023)
In the strategic leadership literature, innovation leadership plays an important role to realize strategic fit in an organization. Strategic fit indicates that the strategic planning made by the organization is in accordance with the vision and mission of the organization, thus having an impact on its business performance. This study aims to investigate the mediating role of strategic fit on the relationship between innovation leadership and organizational performance. The population in this study were cooperatives in Lima Puluh Kota Regency with a sample size of 134 cooperatives. Research data were collected through questionnaires. The partial least square- structural equation modeling method with Smartpls 4 was used to analyze the data. The results of this study confirmed that innovation leadership has a positive and significant influence on strategic fit. Strategic fit exerts a positive and significant influence on organizational performance. This study also found the mediating effect of strategic fit on the relationship between innovation leadership and organizational performance